VALUASI EKONOMI WISATA DENGAN PENDEKATAN INDIVIDUAL TRAVEL COST METHOD (ITCM) PADA TAMAN WISATA AIR WENDIT KABUPATEN MALANG - Sianturi, Putri Haryati Br; Shofwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Natural resources provide benefits to humans in the form of tangible and intangible benefits. One of the indirect or tangible benefits (value) provided by nature is tourism which is generally called nature tourism. Malang Regency is an area that has a large potential for natural tourism destinations. One of the natural attractions or baths in Malang Regency is the Wendit Water Park, which is located in Mangliawan Village, Pakis District, Malang Regency. This tourist attraction has enormous potential with a very unique attraction. However, the management and development is still not optimal so that visitors who come tend to stagnate or do not increase every year. An analysis is needed to determine the magnitude of the benefits provided by the Wendit Water Park. The approach used to assess these benefits is the Individual Travel Cost Method (ITCM). This approach aims to determine the effect of independent variables on tourist visits and to measure the economic value. The variables used are distance, income, travel costs, number of groups, and similar tourism substitutions which were analyzed using multiple linear regression analysis. The economic value or benefits provided by the Wendit Water Park is calculated by knowing in advance the consumer surplus received. The results of this study found that the number of tourist visits at Wendit Air Tourism Park was influenced by the variables of distance, travel costs, number of groups, and substitution of similar tours with a significance level of 5%. Meanwhile, the consumer surplus value generated is an average of IDR436,893 per person per year in one visit. So, the economic value of Wendit Water Pakr is an average of IDR102,903,155,862 per year with an interval of IDR59,524,388,014 to IDR158,081,234,974, - per year.Natural resources provide benefits to humans in the form of tangible and intangible benefits. One of the indirect or tangible benefits (value) provided by nature is tourism which is generally called nature tourism. Malang Regency is an area that has a large potential for natural tourism destinations. One of the natural attractions or baths in Malang Regency is the Wendit Water Park, which is located in Mangliawan Village, Pakis District, Malang Regency. This tourist attraction has enormous potential with a very unique attraction. However, the management and development is still not optimal so that visitors who come tend to stagnate or do not increase every year. An analysis is needed to determine the magnitude of the benefits provided by the Wendit Water Park. The approach used to assess these benefits is the Individual Travel Cost Method (ITCM). This approach aims to determine the effect of independent variables on tourist visits and to measure the economic value. The variables used are distance, income, travel costs, number of groups, and similar tourism substitutions which were analyzed using multiple linear regression analysis. The economic value or benefits provided by the Wendit Water Park is calculated by knowing in advance the consumer surplus received. The results of this study found that the number of tourist visits at Wendit Air Tourism Park was influenced by the variables of distance, travel costs, number of groups, and substitution of similar tours with a significance level of 5%. Meanwhile, the consumer surplus value generated is an average of IDR436,893 per person per year in one visit. So, the economic value of Wendit Water Pakr is an average of IDR102,903,155,862 per year with an interval of IDR59,524,388,014 to IDR158,081,234,974, - per year.